1991
DOI: 10.1007/bf00957893
|View full text |Cite
|
Sign up to set email alerts
|

Fetal mouse kidney maturation in vitro: Coordinated influences of epidermal growth factor, transferrin and hydrocortisone

Abstract: We have investigated the individual and combined actions of epidermal growth factor (EGF), transferrin and hydrocortisone on the maturation of whole fetal mouse metanephroi maintained in serum-free conditions for up to 5 days. The presence of EGF (100 ng/ml) resulted in elevated levels of [3H]-thymidine incorporation when compared to controls; autoradiograms showed that the proliferation of mesenchymal cells in the nephrogenic zone is particularly enhanced as verified by cell counting. Brush border hydrolase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…1(A)) but lower amounts (1-5 ng/ml) of both factors exerted no significant effect on this parameter. It is interesting to note that similar results were obtained in the presence of EGF and TGFα when using fetal mouse kidneys [11,12]. Furthermore, we observed that the addition of an anti-EGF receptor antibody (monoclonal from Calbiochem) to the culture medium neutralized the effect of exogenous EGF and even decreased basal 3 H-thymidine incorporation (Fig.…”
Section: Dna Synthesis In Human Fetal Kidney Explantssupporting
confidence: 83%
See 2 more Smart Citations
“…1(A)) but lower amounts (1-5 ng/ml) of both factors exerted no significant effect on this parameter. It is interesting to note that similar results were obtained in the presence of EGF and TGFα when using fetal mouse kidneys [11,12]. Furthermore, we observed that the addition of an anti-EGF receptor antibody (monoclonal from Calbiochem) to the culture medium neutralized the effect of exogenous EGF and even decreased basal 3 H-thymidine incorporation (Fig.…”
Section: Dna Synthesis In Human Fetal Kidney Explantssupporting
confidence: 83%
“…Nephronic epithelium represented another target of their stimulatory action on DNA synthesis, although it exhibited a weaker responsiveness. Knowing that EGF exerts similar activities on fetal mouse kidneys in organ culture [12] or after EGF injection in infant mice [7], we would like to propose that the fetal form of EGF plays an ubiquitous role by contributing to the regulation of metanephrogenesis in mammalian species. This idea is opposed to our recent finding that another growth factor, namely insulin, might act differentially in human and mouse as a promoter of renal cell proliferation (to be published).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional differentiation of nephron epithelia on the one hand depends on humoral factors such as vitamin A derivates [9]and growth factors or hormones [10, 11, 12, 13], and on the other hand on structural elements such as the extracellular matrix [4]. In addition to these very heterogeneous developmental stimuli it was shown for MDCK cells that also changes in the pH and osmolarity are able to evoke differentiation [14, 15, 16, 17].…”
Section: Humoral and Environmental Factors Modulate Differentiationmentioning
confidence: 99%
“…By showing the actual presence of the TGFα gene transcript and TGFα peptide throughout rat kidney organogenesis as well as in the very early crucial phases of human metanephros development, the present data demonstrate that specific cells of renal primordia actively synthesize TGFα suggesting that this growth factor influences not only the in vitro induced tubulogenesis [7, 17, 18]but also controls in vivo nephrogenic processes throughout the distinct steps of renal organogenesis in cooperation with other growth factors and extracellular matrix molecules [19]. …”
Section: Discussionmentioning
confidence: 99%